2020
DOI: 10.36456/penamas.vol4.no1.a2426
|View full text |Cite
|
Sign up to set email alerts
|

Penguatan Promosi Desa Wisata Berbasis Kearifan Di Desa Pujon Kabupaten Malang

Abstract: Abstract Tourism village is largely based in local wisdom is a form of integrated activities between attractions, accommodation, supporting facilities and additional facilities in the form of village management presented in the structure of community life that is bound by traditional procedures and norms that apply in the village. The development of sustainable tourism villages reguires the participation of local communities in all phases of development starting from the planning, implementation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
1
0
0
1
Order By: Relevance
“…The study found that KLMTV maximized all available resources, including utilizing the residents' houses as bed and breakfast lodgings, serving menus of regional specialties to visitors, performing local cultures and giving educational tours on making regional specialties such as herbal medicine and Tiwul snacks. The results of this study support the studies of Pantiyasa and Supartini (2016), Wisudawati and Maheswari (2018), Suteja, Wahyuningsih, and Masyhudi (2019), Widyastuty, Rukmana, and Tribhuwaneswari (2020) which shows that one of the driving factors behind the development of a tourism village was the potential of regional resources. This finding is also in line with the research results by Soemardiono et al (2021) and Lasally et al (2021) claiming that community support is a determining factor in the development of a tourism village.…”
Section: Discussionsupporting
confidence: 86%
“…The study found that KLMTV maximized all available resources, including utilizing the residents' houses as bed and breakfast lodgings, serving menus of regional specialties to visitors, performing local cultures and giving educational tours on making regional specialties such as herbal medicine and Tiwul snacks. The results of this study support the studies of Pantiyasa and Supartini (2016), Wisudawati and Maheswari (2018), Suteja, Wahyuningsih, and Masyhudi (2019), Widyastuty, Rukmana, and Tribhuwaneswari (2020) which shows that one of the driving factors behind the development of a tourism village was the potential of regional resources. This finding is also in line with the research results by Soemardiono et al (2021) and Lasally et al (2021) claiming that community support is a determining factor in the development of a tourism village.…”
Section: Discussionsupporting
confidence: 86%
“…Banyaknya potensi alam dan manusiasangat mendukung gerakan pariwata dengan pemanfaatan potensi dari hasil industri kecil, pertaniandan perkebunan untukdiintegrasikan dengan wisata desa tematik yang tetap memperhatikan norma dan kearifan lokal. Kegiatan wisata berbasis kearifan lokal melibatkan partisipasi masyrakat secara aktif (Nuurlaily et al, 2020). Partisipasi masyarakat Desa Kwang Rundun saat ini dalam pariwisata terbilang sudah mulai menggeliat, dengan adanya komunitas kelompok sadar wisata Desa Kwang Rundun yang disahlan tahun 2018.…”
Section: Partisipasi Masyarakat Lokalunclassified